The Notion of Contract Segmentation A Comparative Study in Civil Law - Hussain, Esmail Namiq; Hussein, Khalid Khorsheed (Journal of Legal and Political Studies, 2020)
The notion of segmentation of the contract is an important subject in the Civil Code, because of its particularity, as it is an exemption to the obligation of the implementation of the contract as a whole, and although it leads to the inability of producing the contract and its effects, but for some of its effects, despite that, it is an important Instrument that cannot be dispensed of and without which maintaining the life of the contract cannot occur, further, so that to avoid sacrificing the proper part because of the defect of the other part, whether the contract is defected as invalid or annulled, this research has depended on and by adopting comparative Research/Analytical Methods between the position of comparative laws for the subject of the research, we observed that the idea of segmentation of the contract and its applications are found in different texts of the codified and comparative civil laws, but its applications have not been collected under the name of a complete theory, therefore, we recommend that the Iraqi legislator should organize the idea of Segmentation of the contract, and that is by collecting its applications and their terms and conditions, scope and the legal basis on which the theory is based on as a complete theory. and the stability of the legal centers of contractors, and to reduce jurisprudence and jurisprudence. This is because of the role that this legal concept contributes to the preservation of the life of the contract and the stability of the legal centers of the contractors, and to reduce judicial and jurisprudential interpretations.
Keywords: segmentation of the contract; Civil Code; jurisprudence; jurisprudential interpretations; exemption to the obligation